Essays on the Frontiers of Modern Astrophysics and Cosmology - Mathew, Santhosh (Popular Astronomy,, 2014)
This book is a collection of engaging and intriguing essays that describe an intellectual journey from the beginning to the end of universe. It is the product of an ongoing effort to know our place in the universe and share with readers the underpinnings of the magnificent cosmos where we are given a chance to exist only very briefly. The essays incorporate a group of challenging ideas that modern physics and cosmology are struggling to understand, in a unique way that incorporates mythological, religious, and philosophical perspectives. The author relies on a simple and powerful philosophy that we are part of the universe and the universe is part of us.   This wonderful collection of essays provides a journey through the current frontiers of modern astrophysics and cosmology. Its depiction of the most important unsolved mysteries about our place in the Universe is peppered with original insights and philosophical perspectives, making it an intellectual treat. - Avi Loeb, Professor, Harvard University Chair, Astronomy Department; Director, Institute for Theory and Computation   In these essays, Santhosh Mathew combines an impressive knowledge of physics with an eye to its connection to Eastern philosophy as well as its relevance to our life in modern times. In his thoughtful investigation of natural phenomena and their relationship to universal philosophical truths, he takes up where The Tao of Physics leaves off. You may well find his keen curiosity about the natural world and our place in it infectious. - Carole Bugge (C. E. Lawrence), author of Strings   In this informative assemblage of engaging essays Santhosh Mathew takes the reader on a deeply human quest for truth, a truly inspiring journey that boldly addresses the big questions of what the Universe is, how it came into being, and where it may be heading. This exciting adventure is as much a rich scientific history of elegant physics, mathematics, and cosmology as it is a philosophical and spiritual pursuit fueled by human imagination. In this age of globalization Mathew recognizes that we need a new and a more whole story, a new epistemology that links our current and cutting edge intellectual scientific understanding of the physical Universe with our deeply spiritual, mystical, and philosophical insights, and he skillfully weaves the foundation for such a story, leaving the reader with a sense of awe, wonder, power, humility, and belonging. - David Morimoto, Division Director, Natural Sciences and Mathematics, Lesley University.